KOMPETENSI PROFESIONAL GURU BIMBINGAN DAN KONSELING DALAM PENGELOLAAN PROGRAM LAYANAN BIMBINGAN DAN KONSELING DI SMP NEGERI 17 KOTA BANDA ACEH - Khairiah, Yusrizal, Khairuddin (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: One of the determining factors by the implementation of guidance and counseling management as well as by the program services that lead to the success is to improve the competency and professionalism of its teachers. The objective of this study is to determine the competency and professionalism of guidance and counseling teachers in three key aspects: in planning, implementation, and evaluation. Sample was restricted to the services of the guidance and counseling program at state junior high school 17 or SMPN 17 in Banda Aceh and this study involved the principal, vice principal, guidance and counseling teachers, and the chairman of guidance and counseling forum (or abbreviated as MGBK in bahasa) as subjects. The method applied in this research was descriptive method with qualitative approach. The data collection techniques were observation, interview, and documentation.  The results showed that: 1) the competency and professionalism of guidance and counseling teachers are considered based on their abilities in planning of various program and services oriented to guidance and counseling e.g. sharing of information, placement and distribution, understanding the content, group and individual counseling, mediation services, and individual planning; 2) the implementation related to guidance and counseling services are counted based on the operation of basic services e.g. guidance in class rooms, individual or group counseling, consultation, mediation, or any individual services outside the school hours e.g. home visits, or referral; 3) the competency and professionalism of guidance and counseling teachers should also be enhanced not only in evaluation skills related to services but also in terms of problem formulation, data-collection, -instrument and -analysis, as well as in planning the follow-up programs.Keywords: capacity building, counseling, education, junior high school, management Abstrak: Salah satu faktor yang menentukan keberhasilan pelaksanaan program layanan bimbingan dan konseling adalah kompetensi profesional guru bimbingan konseling dalam pengelolaan program bimbingan dan konseling. Penelitian ini bertujuan untuk mengetahui kompetensi profesional guru bimbingan dan konseling dalam perencanaan, pelaksanaan dan evaluasi program layanan bimbingan dan konseling di SMP Negeri 17 Kota Banda Aceh. Adapun metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data adalah observasi, wawancara dan dokumentasi. Subjek penelitian adalah kepala sekolah, wakil kepala sekolah, ketua MGBK dan guru bimbingan dan konseling. Hasil penelitiannya menunjukkan bahwa: (1) Kompetensi profesional guru bimbingan dan konseling adalah merencanakan program layanan orientasi, layanan informasi, layanan penempatan dan penyaluran, layanan penguasaan konten, layanan bimbingan kelompok, layanan konseling individual, konseling kelompok, layanan mediasi, dan perencanaan individual; (2) Pelaksanakan program layanan bimbingan yaitu dengan melaksanakan layanan dasar  bimbingan di dalam kelas, melaksanakan layanan konseling individual, konseling kelompok, konsultasi, mediasi, referal, kunjungan rumah serta layanan perencanaan individual di luar jam pelajaran; (3) Kompetensi profesional guru bimbingan dan konseling dalam mengevaluasi program layanan bimbingan dan konseling dengan merumuskan masalah dan instrumen pengumpul data, menganalisis data serta melaksanakan tindak lanjut.        Kata kunci : Kompetensi profesional , guru,  program bimbingan dan konseling